Religious pluralism in Punjab - Singh, Joginder, author.
1 online resource (432 pages)
Keywords: "This book analyses the heterogeneous modes of meditation, prayer, initiation, beliefs and practices, codes of conduct, ethics and life-style of the contemporary Sikh Sants, Babas, Gurus and Satgurus in Punjab. "--Provided by publisher.